Natural iron fertilization by the Eyjafjallajökull volcanic eruption. Issue 5 (14th March 2013) - Achterberg, Eric P.; Moore, C. Mark; Henson, Stephanie A.; Steigenberger, Sebastian; Stohl, Andreas; Eckhardt, Sabine; Avendano, Lizeth C.; Cassidy, Michael; Hembury, Debbie; Klar, Jessica K.; Lucas, Michael I.; Macey, Anna I.; et al.
Abstract: [1] Aerosol deposition from the 2010 eruption of the Icelandic volcano Eyjafjallajökull resulted in significant dissolved iron (DFe) inputs to the Iceland Basin of the North Atlantic. Unique ship‐board measurements indicated strongly enhanced DFe concentrations (up to 10 nM) immediately under the ash plume. Bioassay experiments performed with ash collected at sea under the plume also demonstrated the potential for associated Fe release to stimulate phytoplankton growth and nutrient drawdown. Combining Fe dissolution measurements with modeled ash deposition suggested that the eruption had the potential to increase DFe by >0.2 nM over an area of up to 570, 000 km 2 . Although satellite ocean color data only indicated minor increases in phytoplankton abundance over a relatively constrained area, comparison of in situ nitrate concentrations with historical records suggested that ash deposition may have resulted in enhanced major nutrient drawdown. Our observations thus suggest that the 2010 Eyjafjallajökull eruption resulted in a significant perturbation to the biogeochemistry of the Iceland Basin. Key Points: Volcanic ash deposition results in enhanced iron and aluminium in Iceland Basin Ash derived iron supply causes nitrate drawdown in seasonal HNLC region Ash stimulates phytoplankton growth in bioassay experiment